De Chatteraar. (Antwerpen : Chatterbox, 1983)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : Dr. M. Timmermanslaan 107, 2060 Merksem
Zie voor 02(1983) 5 het Atthis-tijdschrift Knalpot 05(1983-1984) 7
V.A. De nieuwe chatteraar
V.A. Betty Boop News
Nederlands
Keywords: vrouwencafé